N-Heterocyclic carbene-catalyzed direct cross-aza-benzoin reaction: Efficient synthesis of α-amino-β-keto esters - Uno, Takuya; Kobayashi, Yusuke; Takemoto, Yoshiji (Beilstein Journal of Organic Chemistry, 2012)
An efficient catalytic synthesis of α-amino-β-keto esters has been newly developed. Cross-coupling of various aldehydes with α-imino ester, catalyzed by N-heterocyclic carbene, leads chemoselectively to α-amino-β-keto esters in moderate to good yields with high atom efficiency. The reaction mechanism is discussed, and it is proposed that the α-amino-β-keto esters are formed under thermodynamic control.
Keywords: α-amino-β-keto esters; cross-aza-benzoin; α-imino ester; N-heterocyclic carbenes; organocatalysis; umpolung reactions

(untitled) - Ojika, M.; Inukai, Y.; Kito, Y.; Hirata, M.; Iizuka, T.; Fudou, R. (Chem.–Asian J., 2008)

(untitled) - Sanz-Cervera, J. F.; Blasco, R.; Piera, J.; Cynamon, M.; Ibáñez, I.; Murguía, M.; Fustero, S. (J. Org. Chem., 2009)

(untitled) - Phansavath, P.; Duprat de Paule, S.; Ratovelomanana-Vidal, V.; Genêt, J.-P. (Eur. J. Org. Chem., 2000)

(untitled) - Miyake, F.; Hashimoto, M.; Tonseingsom, S.; Yakushijin, K.; Horne, D. A. (Tetrahedron, 2010)

(untitled) - Wipf, P.; Miller, C. P. (J. Org. Chem., 1993)

(untitled) - Nemoto, T.; Harada, T.; Matsumoto, T.; Hamada, Y. (Tetrahedron Lett., 2007)

(untitled) - Singh, J.; Gordon, T. D.; Earley, W. G.; Morgan, B. A. (Tetrahedron Lett., 1993)

(untitled) - Noyori, R.; Tokunaga, M.; Kitamura, M. (Bull. Chem. Soc. Jpn., 1995)

(untitled) - Makino, K.; Goto, T.; Hiroki, Y.; Hamada, Y. (Tetrahedron: Asymmetry, 2008)

(untitled) - Hamada, Y.; Makino, K. (J. Synth. Org. Chem., Jpn., 2008)

(untitled) - Liu, Z.; Shultz, C. S.; Sherwood, C. A.; Krska, S.; Dormer, P. G.; Desmond, R.; Lee, C.; Sherer, E. C.; Shpungin, J.; Cuff, J.; Xu, F. (Tetrahedron Lett., 2011)

(untitled) - Maeda, T.; Makino, K.; Iwasaki, M.; Hamada, Y. (Chem.–Eur. J., 2010)

(untitled) - Seashore-Ludlow, B.; Villo, P.; Häcker, C.; Somfai, P. (Org. Lett., 2010)

(untitled) - Hamada, Y.; Koseki, Y.; Fujii, T.; Maeda, T.; Hibino, T.; Makino, K. (Chem. Commun., 2008)

(untitled) - Suzuki, M.; Iwasaki, T.; Miyoshi, M.; Okumura, K.; Matsumoto, K. (J. Org. Chem., 1973)

(untitled) - Krysan, D. J. (Tetrahedron Lett., 1996)

(untitled) - Schultz, K.; Stief, L.; Kazmaier, U. (Synthesis, 2012)

(untitled) - Hara, O.; Ito, M.; Hamada, Y. (Tetrahedron Lett., 1998)

(untitled) - Bertelsen, S.; Nielsen, M.; Bachmann, S.; Jørgensen, K. A. (Synthesis, 2005)

(untitled) - Bourdon, L. H.; Fairfax, D. J.; Martin, G. S.; Mathison, C. J.; Zhichkin, P. (Tetrahedron: Asymmetry, 2004)

(untitled) - Moody, C. J.; Swann, E. (Synlett, 1998)

(untitled) - Mordant, C.; Dünkelmann, P.; Ratovelomanana-Vidal, V.; Genet, J.-P. (Chem. Commun., 2004)

(untitled) - Yu, J.; Liu, S.-S.; Cui, J.; Hou, X.-S.; Zhang, C. (Org. Lett., 2012)

(untitled) - Enders, D.; Niemeier, O.; Henseler, A. (Chem. Rev., 2007)

(untitled) - Marion, N.; Díez-González, S.; Nolan, S. P. (Angew. Chem., Int. Ed., 2007)

(untitled) - Phillips, E. M.; Chan, A.; Scheidt, K. A. (Aldrichimica Acta, 2009)

(untitled) - Moore, J. L.; Rovis, T. (Top. Curr. Chem., 2010)

(untitled) - Chiang, P.-C.; Bode, J. W. (TCI Mail, 2011)

(untitled) - Vora, H. U.; Rovis, T. (Aldrichimica Acta, 2011)

(untitled) - Hirano, K.; Piel, I.; Glorius, F. (Chem. Lett., 2011)

(untitled) - Biju, A. T.; Kuhl, N.; Glorius, F. (Acc. Chem. Res., 2011)

(untitled) - Nair, V.; Menon, R. S.; Biju, A. T.; Sinu, C. R.; Paul, R. R.; Jose, A.; Sreekumar, V. (Chem. Soc. Rev., 2011)

(untitled) - Cohen, D. T.; Scheidt, K. A. (Chem. Sci., 2012)

(untitled) - Bugaut, X.; Glorius, F. (Chem. Soc. Rev., 2012)

(untitled) - Castells, J.; López-Calahorra, F.; Bassedas, M.; Urrios, P. (Synthesis, 1988)

(untitled) - Murry, J. A.; Frantz, D. E.; Soheili, A.; Tillyer, R.; Grabowski, E. J. J.; Reider, P. J. (J. Am. Chem. Soc., 2001)

(untitled) - Frantz, D. E.; Morency, L.; Soheili, A.; Murry, J. A.; Grabowski, E. J. J.; Tillyer, R. D. (Org. Lett., 2004)

(untitled) - Mattson, A. E.; Scheidt, K. A. (Org. Lett., 2004)

(untitled) - Mennen, S. M.; Gipson, J. D.; Kim, Y. R.; Miller, S. J. (J. Am. Chem. Soc., 2005)

(untitled) - Li, G.-Q.; Dai, L.-X.; You, S.-L. (Chem. Commun., 2007)

(untitled) - Enders, D.; Henseler, A.; Lowins, S. (Synthesis, 2009)

(untitled) - DiRocco, D. A.; Rovis, T. (Angew. Chem., Int. Ed., 2012)

(untitled) - DiRocco, D. A.; Rovis, T. (J. Am. Chem. Soc., 2012)

(untitled) - Baragwanath, L.; Rose, C. A.; Zeitler, K.; Connon, S. J. (J. Org. Chem., 2009)

(untitled) - O'Toole, S. E.; Rose, C. A.; Gundala, S.; Zeitler, K.; Connon, S. J. (J. Org. Chem., 2011)

(untitled) - Jin, M. Y.; Kim, S. M.; Han, H.; Ryu, D. H.; Yang, J. W. (Org. Lett., 2011)

(untitled) - Mao, H.; An, S. L.; Kim, S. M.; Yang, J. W. (Bull. Korean Chem. Soc., 2011)

(untitled) - Kim, S. M.; Jin, M. Y.; Kim, M. J.; Cui, Y.; Kim, Y. S.; Zhang, L.; Song, C. E.; Ryu, D. H.; Yang, J. W. (Org. Biomol. Chem., 2011)

(untitled) - Rose, C. A.; Gundala, S.; Fagan, C.-L.; Franz, J. F.; Connon, S. J.; Zeitler, K. (Chem. Sci., 2012)